Multilevel marketing: problems and prospects - Stasuk, Natalia; Stasuk, Oleksandr; Yakovenko, Regina (Skhid, 2013)
In the article the trends of direct selling branch was dissected, the main development problems of multilevel marketing as an organization form of trade activity and its future prospect in the retail system was identified